Odontonia kerangcaris sp. nov., a new bivalve-associated shrimp (Crustacea, Decapoda, Palaemonidae) from East Kalimantan, revealing intrageneric host switching - Fransen, Charles H.j.m.; Groenhof, Mike; de Gier, Werner (Zootaxa, 2021)
A new species of bivalve mollusk dwelling palaemonid shrimp of the genus Odontonia is described from the Berau Islands, East Kalimantan, Indonesia. This is the only Odontonia species recorded as a symbiont of a bivalve mollusk, all other congeners are known to associate with solitary ascidians. The new species belongs to the group wherein the dactylus of the ambulatory pereiopods has an accessory tooth. It differs from these species in the absence of a forward directed proximal tooth on the flexor margin of the corpus of the ambulatory dactyli. It also lacks the small denticles posterior to the distoventral accessory tooth on the dactylar corpus.